ANALISIS PENGATURAN DAN TUJUAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PADA PENANAMAN MODAL DI INDONESIA - Ratih Kesuma Dewi, Ni Nyoman; Sarna, Kadek (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 03, Juni 2014, 2014)
Corporate social responsibility based on the reason that the company's activities impact the environment and social economic conditions of the community. This paper describes the analysis of arrangements and goal of Corporate Social Responsibility (CSR) on investment in Indonesia. In writing scholarly journals used this type of research is normative research. In Regulation of CSR, there are differences regarding the concept of CSR can be seen from the definition and the scope of CSR and corporate business sectors are required to implement CSR. The purpose of CSR on investment in Indonesia is not only to look for profit, but reduces the unethical business practices and minimize the negative impacts of the business production process to the public that will create a conducive investment climate especially on the environment.
Keywords: Responsibility, Social, Corporate, Environment, Investment